Penjualan Online dalam Perspektif Syariah - Ya'qub, Mohammad (Jurnal Studi Multidisiplin Qomaruna, 2023)
This article aims to investigate online retail transactions through the lens of Islamic Sharia law. Utilizing a library-based research approach, this study specifically examines the phenomenon of tiktok online shop. One of the key findings is that such online transactions frequently manifest elements of "ghoror" (ambiguity), leading to uncertainty in contractual agreements and raising concerns of "syubhat" (dubiousness). According to Islamic teachings, as outlined by Prophet Muhammad, lawful trade must occur based on mutual consent or "Antaradhin." Consequently, online businesses failing to meet these criteria are considered impermissible due to the presence of "ghoror." The study emphasizes the need for proper contractual agreements in online transactions to prevent either party from experiencing detriment.